SUSTAINABILITY AWARENESS IN INDONESIA’S OIL AND GAS SECTOR - Anggraini, Gita; Hermawan, Ancella (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
PT XYZ, the largest oil and gas producer in Indonesia, demonstrates its commitment to sustainability through initiatives such as a zero-flaring target and renewable energy projects. However, its ESG Risk Rating increased from 20.7 to 26.7 (medium risk), indicating challenges in managing environmental and social aspects that may relate to internal sustainability awareness. This study evaluated the sustainability awareness of working-level employees using the levers of control framework, with a focus on belief systems and stakeholder theory. A mixed-methods approach was employed, combining quantitative data from surveys of 75 employees and qualitative insights from semi-structured interviews with management. The analysis covered understanding of sustainability concepts, belief systems implementation, and awareness of the triple bottom line dimensions. Findings showed that belief systems communication had enhanced awareness to a moderately high level, though broader and more systematic education is needed to strengthen awareness across the organization.